IDENTIFIKASI BAKTERI ASAM LAKTAT PADA JEROAN PEDA IKAN KEMBUNG (Rastrelliger sp.) SEBAGAI AGEN PROBIOTIK - Hasanah, Uswatun (JURNAL PENELITIAN SAINTIKA, 2014)
This study aims to determine the types and characteristics of lactic acid bacteria contained in the innards Peda Mackerel. The research was conducted in April to June 2013 in the Microbiology Laboratory Biology Departement FMIPA UNIMED. This study uses descriptive. Sampling techniques in aseptic. Materials used are lactic acid bacteria taken from the innards Peda Mackerel and grown on MRS medium (de Man Rogosa Sharpe). Based on the research results of the identification and characterization of lactic acid bacteria in Peda Mackerel using Test morphology, Gram staining and Biochemical tests of the obtained 2 types of lactic acid bacteria on the innards Peda Mackerel. The genus of lactic acid bacteria found include Lactobacillus and Streptococcus. Characteristics in general is a form of cocci and bacilli, Gram positive, catalase negative, non motile, the optimum temperature of 20 L 0C-400C and both have type homofermentatif fermentation. Genus agency that acts as a probiotic is genus Lactobacillus, while the genus Streptococcus can not act as an agency probiotics because it does not have the ability of to survive in the digestive tract.